1998
DOI: 10.1111/j.2044-8295.1998.tb02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of risk in motorcyclists: Unrealistic optimism, relative realism and predictions of behaviour

Abstract: In the first phase of a prospective investigation, a national sample of motorcyclists completed a postal questionnaire about their perceptions of risk, their behaviour on the roads and their history of accidents and spills. In the second phase a year later, they reported on their accident history and behaviour over the preceding 12 months. A total of 723 respondents completed both questionnaires. Four sets of findings are reported. First, the group as a whole showed unrealistic optimism: on average, respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
91
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 34 publications
9
91
1
2
Order By: Relevance
“…Based on the hypothesis that risk sport practitioners' perceived comparative risks would be in some way realistic, we expected that participants who like playing to the limit will be conscious of the risk they take and thus will be likely to assess themselves as being more exposed to the risk of injury than the average sportsman (hlypothesis 4). Finally, in line with studies (e.g., Rutter et al, 1998) who found a positive link betv/een accident history and an increased perceived vulnerability, we expected that past injury episodes will be positively linked with perceived comparative VSI (Hypothesis 5).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Based on the hypothesis that risk sport practitioners' perceived comparative risks would be in some way realistic, we expected that participants who like playing to the limit will be conscious of the risk they take and thus will be likely to assess themselves as being more exposed to the risk of injury than the average sportsman (hlypothesis 4). Finally, in line with studies (e.g., Rutter et al, 1998) who found a positive link betv/een accident history and an increased perceived vulnerability, we expected that past injury episodes will be positively linked with perceived comparative VSI (Hypothesis 5).…”
supporting
confidence: 66%
“…Respondents may also express comparative pessimism, perceiving their own VSI as greater, or their own AMR as lower, than that of others, particularly when they have experienced negative events such as accidents (Rutter, Quine, & Albery, 1998) or when they feel they have little personal control over dangers (Harris, 1996). Since the present study focused on sports that involve varying degrees of risk, which remain uncontrollable, we might expect that comparative optimism will not be prevalent amongst risk sports practitioners.…”
mentioning
confidence: 99%
“…Similarly, drivers and motorbike riders under-estimate the chances of having an accident (e.g. Rutter et al, 1998). A prominent explanation is that drivers may suffer from an illusion of control (Weinstein, 1980;1984).…”
Section: Issues In the Measurement Of Employment Insecuritymentioning
confidence: 99%
“…Therefore, generally, riders wear a helmet due to legislative measures, but their personal opinion about the helmet use is questionable. As it turns out, only a few studies examined the use of helmets in conjunction with the riders' personal opinion about the helmets' usefulness (Rutter et al 1998;Pileggi et al 2006;Oginni et al 2007;Germeni et al 2009;Ranney et al 2010). The majority of these studies concluded that riders with no helmets do not truly believe in their protective value.…”
Section: Introductionmentioning
confidence: 99%